Geographical Global Rural Cultures and Cultures in Particular Geographical Realities: Some Particular Ideas for a Global Debate - Paniagua, Angel (Global Journal of Cultural Studies, 2024)
Scientific contributions to global culture are scarce from a rural geographic perspective. The vision of global rural culture is framed between global as a product of particular cultures or as particular cultures contributed to geographically global rural. Furthermore, the emergence of new politics of rural cultures associated with re- and territorialization processes and small tactics in place is analyzed. Finally, the bases are established for the joint and integrated study of the concept and approaches to global rural and global culture in different geographical scenarios in the global South and North.